Ефективність конфліктів в організації - Гриценко, Наталя Валеріївна (НТУ "ХПІ", 2016)
Внутрішні соціальні конфлікти, що зачіпають тільки цілі, цінності та інтереси, які не суперечать прийнятим основам внутрішньогрупових відносин, як правило, носять функціонально позитивний характер. У тенденції такі конфлікти сприяють зміні внутрішньогрупових норм і відносин відповідно до загальних потреб окремих індивідів або підгруп. Якщо ж протиборчі сторони не розділяють більш цінностей, на яких базувалася законність даної системи, то внутрішній конфлікт несе в собі небезпеку розпаду соціальної структури.

Internal social conflicts affecting only the goals, values and interests that do not contradict the fundamentals of intragroup relations adopted as a rule, are functionally positive. In such conflicts contribute trends intercompany changing norms and attitudes according to the common needs of individuals or groups. If the warring parties do not share more values on which was based the legitimacy of the system, the internal conflict carries the danger of collapse of the social structure. Thus, it is destructive properties devastating conflict capabilities make absurd attempt to determine the effectiveness of the universal conflict, irrespective of their opponents and over-organization.
Efficiency of conflict in organizations
Keywords: конфлікт; функції; організація; групоутворення; надорганізація; conflict; functions